OPTIMALISASI PROYEK PENINGKATAN KAPASISTAS DERMAGA PELABUHAN MERAK DENGAN METODE CPM, PERT, DAN TIME COST TRADE OFF OLEH PT. XYZ - Tika Syahdillah Daratu, (2022)
In a development, it is very necessary to plan and schedule in detail about; activities, time and cost required to complete a project. This is done to get optimal results, optimistic time, and efficient costs. In this study, the case study used for the analysis of project time acceleration is the project to increase the capacity of the port of Merak port. This project took 121 days. However, in reality it cannot be denied that in the construction of a project there are several problems that are often faced, one of which is delays. The purpose of this research is to speed up the project completion time efficiently in terms of cost and analyze the effectiveness of the shortened time using the CPM and PERT methods and the Time Cost Trade Off. So that it can be known the minimum acceleration and the minimum cost. The results of this study are 30 critical path activities so that the optimal acceleration duration of the port dock capacity increase project is 24 days from the remaining 49 days of work with an optimal cost of Rp. 14,848,787,998.